Conflict Accommodation Ideas Based on Custom Institutions Siram Sopi in Gold Mining Area of Romang Island, Indonesia - Yamres Pakniany; Febby Nancy Patty (Sodality: Jurnal Sosiologi Pedesaan, 2019)
Conflict over natural resources in mining areas often has impacts on social relations between communities, including that in the gold mining area in Romang Island. The conflict in this area involves various actors. This research was conducted with the aim to find out the accommodation efforts made in reconciling the actors. This research used qualitative methods by observation and interviews, while data analysis was carried out using interactive models. The results showed that conflict accommodation is a process undertaken to reconcile conflicting actors. The sopi flush deed is one of the customary deeds which is usually practiced to reconcile conflicting actors. The sopi flush deed functions to reconcile the conflicting actors in the gold mining area in Romang Island, Southwest Maluku Regency, Indonesia.